Establishment of Seed Production Area of Acacia nilotica (L.) Wild. Ex Del. SSP. Indica (Benth.) Brenan in Gujarat - Mishra, D. K.; Tewari, V. P.; Tripathi, S. P.; Bohra, N. K.; Emmanuel, C. J. S. K. (Indian Forester, 2017)
Developing seed production areas (SPAs) is one of the first steps in tree improvement programme that can be used to obtain genetically improved seed for immediate planting. It is usually for the short term in nature. Though seeds obtained from this method do not yield large volume of genetic gain, it sometimes greatly improves tree quality. After survey of Acacia nilotica ssp. indica plantations at six sites in Godhara, Nadiyad and Junagarh planted by SFD, Gujarat during 1970-84, 25ha. at Gushar (Godhara) and 15 ha. at Pawagarh (Godhara) were converted into SPAs after intercomparing various other seed stands. After scoring each tree in the stand and ranking them in descending order, out of 44,635 trees at Gushar, 30691 plants were culled and 13944 trees were retained while out of 5712 trees at Pawagarh, 1510 were culled and 4212 were retained. After culling, the average height, clear bole, and girth diameter were found to be shifted towards the higher side in both the stands. Seeds collected after establishment of SPA showed improvement in seed weight and germination percentile.